THE ROLE OF TEACHERS IN INCREASING THE READING INTEREST OF ELEMENTARY SCHOOL STUDENTS - Syafira Syafira; Febrina Dafit (IKIP Siliwangi, 2022)
The teacher's role is important in increasing students' reading interest, this is because students tend to prefer playing with peers rather than reading books, especially in today's modern era students use mobile phones. At online times like this, students use cellphones more often so students prefer to play games on cellphones and play tik tok rather than reading. The purpose of this study was to describe the teacher's role in increasing the reading interest of grade 3 students at SD Negeri 42 Pekanbaru, to describe the teacher's obstacles in increasing the reading interest of grade 3 students at SD Negeri 42 Pekanbaru. This research method uses descriptive qualitative research. The research subjects were third grade homeroom teachers and school principals. Collecting data using observation, interview and documentation techniques. The results of this study indicate that the role of teachers as creators, facilitators, motivators, evaluators and dynamicators is very important to increase the reading interest of elementary school students because teachers guide, encourage and monitor students. The obstacle is that the teacher still has not carried out several teacher roles such as the teacher has not carried out the teacher's role as a creator, the teacher's role as an evaluator, the teacher's role as a dynamist completely, this is due to the limited face-to-face learning, for the teacher's role as a facilitator and the teacher's role as a motivator. seems to have been done